IMF Survey, Volume 32, Issue 11. (IMF Survey; IMF Survey ;, 2003)
Against a background of the continuing effects of the sharp declines in recent years in global equity markets, widening output gaps, and weak business and consumer confidence, concerns about deflation in both industrial and emerging market economies have mounted in recent months. With Japan already suffering from deflation and China and several other Asian economies experiencing deflationary pressures, the worry is that these could deepen and even spread more widely. Panelists at a May 29 IMF Economic Forum assessed the risks and debated appropriate policy responses, using a newly released staff report 'Deflation: Determinants, Risks, and Policy Options,' as a springboard. The panel, moderated by Kenneth Rogoff (IMF Economic Counsellor and Director of the Research Department), comprised Laurence Ball (Professor of Economics, Johns Hopkins University), Manmohan S. Kumar (Advisor, IMF Research Department), Vincent Reinhart (Director of Monetary Affairs, U.S. Federal Reserve System Board of Governors), and Kim Schoenholtz (Chief Economist, Citigroup Global Markets). Panelists voiced varying degrees of concern about current risks, but all agreed that the best way to defeat deflation was to prevent it from setting inches.